Organization Theory in Business and Management History: Present Status and Future Prospects. Issue 3 (15th August 2017) - Maclean, Mairi; Harvey, Charles; Clegg, Stewart R.
Abstract : A common lament is that business history has been marginalized within mainstream business and management research. We propose that the remedy lies in part with more extensive engagement with organization theory. We illustrate our argument by exploring the potentialities for business history of three cognitive frameworks: institutional entrepreneurship, evolutionary theory, and Bourdieusian social theory. Exhibiting a higher level of theoretical fluency might enable business historians to accrue scholarly capital within the business and management field by producing theoretically informed historical discourse, demonstrating the potential of business history to extend theory, generate constructs, and elucidate complexities in unfolding relationships, situations, and events.